Mechanism-based pharmacokinetic–pharmacodynamic (PK–PD) modeling and simulation of oxaliplatin for hematological toxicity in rats. (1st February 2020) - Kobuchi, Shinji; Katsuyama, Yosuke; Ito, Yukako
Abstract: Oxaliplatin (L-OHP) is a platinum (Pt)-based anticancer agent and is widely used for treating gastroenterological cancer. However, L-OHP-induced hematological toxicity is a critical undesirable effect that limits the dose of L-OHP. An ideal chemotherapeutic strategy that avoids severe hematological toxicity while maintaining positive chemotherapeutic outcomes has not been established for L-OHP. In this study, a pharmacokinetic–pharmacodynamic (PK–PD) model was developed that can link the associations between L-OHP administration regimens and the risk of hematological toxicity. The plasma concentration of L-OHP and neutrophil, lymphocyte and platelet counts after L-OHP (3, 5, and 8 mg/kg) administration to rats were used to develop the PK–PD model. The mechanism-based PK–PD model comprised a semi-physiological PD model that adequately described and simulated the entire time-course of alterations in blood cell counts. The model-based simulation proposed that a combination of the PK–PD model and monitoring of platelet counts throughout L-OHP-based chemotherapy is a valuable approach to determine an individualized optimal dosing strategy including the washout period. The current results might provide a framework for population PK–PD model analysis using hematological data of patients receiving L-OHP and investigations of chemotherapeutic strategies that are difficult to address in patients.